Neutral Taxation of Shareholder Income: A Norwegian Tax Reform Proposal - Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2003)
A Norwegian tax reform committee recently proposed a personal tax on the realized income from shares after deduction for an imputed risk-free rate of return. This paper describes the design of the proposed shareholder income tax and shows that it will be approximately neutral in several important dimensions, provided that full loss o.sets are granted. Thus the tax allows some non-distortionary double taxation of corporate equity income. With an appropriate choice of tax rates, it also solves the problem of income shifting under a dual income tax. The final part of the paper clarifies the differences between the shareholder income tax and previous proposals for neutral capital income taxation.
Keywords: 330; tax neutrality; shareholder income tax; corporate-personal tax integration